Study to evaluate the add on effect of specific Yoga therapy along with Amalaki Churna in Type 2 Diabetes Mellitus - Solanki, Virendra Singh; Jain, Trupti; Bansal, Charu; Tekam, Vishwanath Singh (International Research Journal of Ayurveda & Yoga, 2024)
The prevalence of Diabetes is rapidly rising all over the globe at an alarming rate.Diabetes Mellitus occurs throughout the world, but it is more common; especially Type-2 Diabetes Mellitus in the developed countries. WHO predicted that at the current rate there will be some 592 million D.M.people by the year 2035.In India, it is estimated that by the year 2017 total number of Diabetic subjects to be around 72.9 and by year 2045 it is further set to rise to 134.3 million (IDF).Various scientific researches showed Yogasanas have great potential in the prevention and the control of lifestyle disorders like metabolic syndrome, asthama, cancer, diabetes and its co-morbid conditions like hypertension and dyslipidemia etc. Simultaneously, various Ayurvedic single herbs proved its potential in the control of Diabetes and its complications by their antioxidant properties and Amalakichurnais one of them.Thus for the present study specific yoga therapyand Amalakichurna were selected for the patients of Type 2 Diabetes Mellitus.Method: For this study total 60 diagnosed patients of type 2 DM were selected from OPD of Dept. of Kayachikitsa, Panchakarma and Swasthavritta of Pt. Khushilal Sharma Govt. Ayurveda,Bhopal.Group A: YogasanaandAmalakiChurnaGroup.Group B: AmalakiChurnaGroup ⮚ Trikonasana, Pawanmuktasana, Janushirshasana, Marichyasana, Setubandhasana, Ushtrasana, Mandukasana, for 7 times early in the morning daily for 45 days. ⮚ In both the groups, Oral administration of AmalakiChurna in 6gm BD dose daily empty stomach with luke warm water for 45 days. ⮚ In both the groups, Pt. advised for restriction of diet according to D.M. Out of these patients 45 were completed the course of treatment and 15 patients were dropout due to inconvenience for regular yoga practice.Statistical analysis of boththe group showed that Yoga therapy and AmalakiChurna provided relief in allsubjective and objective parameter in Type 2DM.On inter group comparison of group A and B,groupA showed better effect than group B. This shows that specific YogaTherapy andAmalakiChurnawaseffective in control of Type 2DM.